Влияние обработки импульсным электрическим током на усталость нержавеющей стали Х18Н10Т - Степанов, Г.В.; Бабуцкий, А.И.; Чижик, А.В.; Грязнов, Б.А.; Налимов, Ю.С. (Видавничий дім "Академперіодика" НАН України, 2008)
It is shown that the treatment with a pulsed high-density electric current causes the increase of the fatigue limit of Kh18N10T steel by more than 50%.